The lignan (+)‐episesamin interferes with TNF‐α‐induced activation of VSMC via diminished activation of NF‐ĸB, ERK1/2 and AKT and decreased activity of gelatinases. (13th October 2014) - Freise, C.; Querfeld, U.
Abstract Aim Activation of vascular smooth muscle cells (VSMC), a key event in the pathogenesis of atherosclerosis, is triggered by inflammatory stimuli such as tumour necrosis factor‐alpha (TNF‐α) causing a mitogenic VSMC response. The polyphenol (+)‐episesamin (ES) was shown to counteract TNF‐α‐induced effects, for example in macrophages. Aiming for novel therapeutic options, we here investigated whether ES protects VSMC from TNF‐α‐induced growth and migration, which both contribute to the onset and progression of atherosclerosis. Methods Human and murine VSMC were treated with combinations of ES and TNF‐α. Expressions of mRNA were analyzed by RT‐PCR. Enzymatic activities and proliferation were determined by specific substrate assays. Cell signalling was analyzed by Western blot and reporter gene assays. Migration was assessed by wound healing assays. Results ES at 1–10 μm reduced basal and TNF‐α‐induced VSMC proliferation and migration due to impaired activation of extracellular signal‐regulated kinases (ERK)1/2, Akt (protein kinase B), nuclear factor‐kappa B (NF‐ĸB) and vascular cell adhesion molecule (VCAM)‐1. This was accompanied by reduced expression and secretion of matrix metalloproteinases (MMP)‐2/‐9, which are known to promote VSMC migration. Specific inhibitors of Akt, NF‐ĸB and MMP‐2/‐9 reduced TNF‐α‐induced VSMC proliferation, confirming ES‐specific effects. Besides, ES reduced TNF‐α‐ and H2O2‐induced oxidative stress and in parallel induces anti‐inflammatory haem oxygenase (HO)‐1 expression. Conclusion ES interferes with inflammation‐associated VSMC activation and subsequent decreased proliferation and migration due to anti‐oxidative properties and impaired activation of NF‐ĸB, known contributors to atherogenesis. These results suggest ES as a complemental treatment of VSMC specific vascular diseases such as atherosclerosis.